Analisis Saluran Tataniaga Beras di Wilayah Kecamatan Singosari Kabupaten Malang - Agistari Linawarti (Jurnal Ekonomi dan Studi Pembangunan, 2015)
The purpose of this study was to determine the form of rice distribution channels, as well as knowing the price received by farmers from the price paid by consumers, and those who enjoy the largest margin in the rice distribution channel. In that condition, confirmed by the obtained policy for rice distribution arrangement that is fair marketing margin. This research was conducted in the area Singosari Malang. Watugede village chosen as a sample, because the village has a community food distribution agency which is a program of the government which became the central point of rice production. The approach is quantitative descriptive analysis. Determination of respondents using purposive sampling is to select a sample of farmers as much as 100 people. Selected farmers based on the consideration of his cultivated rice area and education (ability to provide the required information).  Keywords: rice, business administration, marketing distribution channels